Positive incentives for managing groundwater in the presence of informal water markets: perspectives from India - Balasubramanya, Soumya; Buisson, Marie-Charlotte (IOP Publishing, 2022)
India is the world's largest user of groundwater, the bulk of which is used for irrigation (Hirji et al 2017). Groundwater-based irrigation was an enabling factor for the Green Revolution, which has increased food security and reduced poverty; but with abstraction exceeding recharge, 28% of administrative blocks in India have aquifers classified as over-exploited, critical, or semi-critical (Mukherjee 2018). Governments have recently been attempting to use positive incentives to reward farmers for reducing abstraction, but such policy approaches often ignore the presence of informal groundwater markets (IGMs), where wells owners supply irrigation services to other farmers for a charge, in addition to irrigating their own fields. IGMs may undermine incentive programs; and implementing incentive programs in the presence of IGMs may have unintended welfare consequences. Better data and research on IGMs is needed for managing groundwater in India.